Evidence on Human Exposure to Pesticides and the Occurrence of Health Hazards in the Brazilian Population: A Systematic Review - Panis, Carolina; Kawassaki, Aedra Carla Bufalo; Crestani, Ana Paula Jaqueline; Pascotto, Claudiceia Risso; Bortoloti, Durcelina Schiavoni; Vicentini, Geraldo Emílio; Lucio, Léia Carolina; Ferreira, Mariane Okamoto; Prates, Rosebel Trindade Cunha; Vieira, Valquíria Kulig; Gaboardi, Shaiane Carla; Candiotto, Luciano Zanetti Pessoa (Frontiers in Public Health, 2022)
Brazil is among the biggest pesticide consumers in the world, with its population severely exposed to tons of such substances, both because of environmental contamination and occupational use. The health consequences of pesticide exposure are well-documented, but still sparse regarding Brazilian population. This study systematically reviewed the Brazilian studies published that address the relationship between exposure to pesticides and health problems in the Brazilian population. Also, information about pesticide use in Brazil is provided. The included studies showed that exposure to pesticides has a relevant impact on the health of the Brazilian population, regardless of age and gender, and on workers in rural areas or not. Most poisoning events seem to result from the continuous use of pesticides, whether occupationally or environmentally, characterizing a public health problem. The major consequences reported in literature were damage to the central nervous system, cancer, deleterious effects on rural workers' health, intoxications, malformations, and endocrine changes. These findings point out the need to understand the impact of chronic exposure to pesticides on severely exposed people and highlight the importance of creating public policies to protect them and avoid disease occurrence.